2017
DOI: 10.1080/15548627.2017.1332549
|View full text |Cite
|
Sign up to set email alerts
|

Atg5- and Atg7-dependent autophagy in dopaminergic neurons regulates cellular and behavioral responses to morphine

Abstract: The molecular basis of chronic morphine exposure remains unknown. In this study, we hypothesized that macroautophagy/autophagy of dopaminergic neurons would mediate the alterations of neuronal dendritic morphology and behavioral responses induced by morphine. Chronic morphine exposure caused Atg5 (autophagy-related 5)- and Atg7 (autophagy-related 7)-dependent and dopaminergic neuron-specific autophagy resulting in decreased neuron dendritic spines and the onset of addictive behaviors. In cultured primary midbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 61 publications
(111 reference statements)
3
57
0
Order By: Relevance
“…Overwhelming evidence has elucidated the intricate relationship between apoptosis and autophagy . ATG7 has been reported to be a vital regulator in autophagy . To confirm the interplay between these biological processes, we used 3‐MA (3‐methyladenine) and ATG7 siRNA to pharmacologically and genetically block autophagy.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overwhelming evidence has elucidated the intricate relationship between apoptosis and autophagy . ATG7 has been reported to be a vital regulator in autophagy . To confirm the interplay between these biological processes, we used 3‐MA (3‐methyladenine) and ATG7 siRNA to pharmacologically and genetically block autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, emerging studies have demonstrated a link between autophagy and apoptosis . Atg7, an essential autophagy regulator, plays important roles in disease development and progression . In this study, we used ATG7 siRNA and 3‐MA to inhibit autophagy and explore the potential role of autophagy in NaB‐induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations